As cidades sustentáveis e a sustentabilidade urbana: caminhos para a (des)judicialização da saúde - Picon, Leila Cássia (2017)
The present research starts from the problematic about sustainable cities as an instrument for the (de) judicialization of health demands. The general objective of this research is to analyze whether preventive public policies, encompassed in sustainable cities, will reduce the high number of curative actions promoted by health judicialization. The subject is extremely relevant and totally in line with the research line, since it is the duty of the State, through public policies, to concretize social rights, in particular, to ensure the fundamental right to health, especially related issues Preventive health and protection of the environment, through the so-called sustainable growth. The specific objectives to be pursued are aimed at analyzing the fundamental right to health and the problems related to their promotion and prevention, adoption of collective protection measures whenever necessary and as a priority, and providing society with clear and accurate information on the most Adequate to reduce health risks, as well as examining the role of public policies in the cities for health promotion and assessing the role of the judiciary in the judicialization of the right to health against the duties and limits of the State in the positivization and applicability . For the development of this dissertation, the analytical method was used as the methodological method and the monographic method, through the descriptive-analytical bibliographical research, using legislation, legal doctrines and specialized jurisprudence more appropriate to the object of the study. Based on the study, it was possible to conclude that when cities invest in preventive health, through public policies focused on sustainability, it is directly contributing to an improvement in the quality of life of the population and consequently leading to a significant reduction of curative actions, Which present a high cost and little effectiveness. We do not need bigger cities, we need better cities that have a watchful eye for sustainable development and for public policies that express the real needs of the citizen.